Modeling and Investigation of the LDPC Immunity Code to Provide Increased Immunity in the Dvb-T2 Standard Digital Television System - A.A. Yarmukhamedov; A.B. Jabborov (Zien Journals, 2023)
In this paper, an error-correcting LDPC code has been investigated and modeled to provide an increase in noise immunity in a digital television system of the DVB-T2 standard. The algorithm of functioning of the noise-correcting LDPC codec was studied theoretically and practically. The noisecorrecting LDPC code in the digital television system of the DVB-T2 standard with the developed interactive computer simulation program in the Matlab/Simulink programming language, the dependence of the number of errors on the error probability for the noise-correcting LDPC code was modeled and investigated.
Keywords: LDPC code; error-correcting code; DVB-T2 standard; encoder and decoder